Maqashid Syari'ah in Sharia Economic Law: The Loss of Down Payment According to the Maqashid Syari'ah Review - Imam Kamaluddin; Ilham Aulia Fatani (al-Afkar, Journal For Islamic Studies, 2026)
This study discusses the Background of the Problem In fulfilling their needs, humans are governed by laws that have been determined by Allah SWT. Law in Islam is a rule relating to the relationship between individuals and other individuals, as well as individuals and their creator. Therefore, Allah SWT reminds us that in fulfilling their needs, humans do not harm each other, in this case exchanging needs between members of society is a fair way. The rules of Allah that are unified and codified in the fiqh of mu'amalah cover several aspects of economic activities, one of which is buying and selling (al-ba'i). Buying and selling or referred to as Bai' is the exchange of property for property on the basis of mutual consent, or transferring property with a justified exchange. According to Sulaiman al-Asyqar, buying and selling is the exchange of property for property, or benefits for benefits in the form of transferring ownership and ownership. The term down payment is also known as DP (Down of Payment), advance payment, or down payment. In Indonesia this is regulated in Article 1464 of the Civil Code. The payment of a down payment or down payment in a buying and selling transaction is known by fiqh scholars as ba'i 'urbun. Ba'i 'urbun is a down payment paid by the buyer which shows that he is serious about his order. If the buyer then agrees on the ordered goods, a sale and purchase transaction is formed and the down payment is part of the agreed price of the ordered goods (assets). If the buyer later refuses to purchase the order, then the down payment is forfeited and becomes the property of the seller. This study discusses the Background of the Problem In fulfilling their needs, humans are governed by laws that have been determined by Allah SWT. Law in Islam is a rule relating to the relationship between individuals and other individuals, as well as individuals and their creator. Therefore, Allah SWT reminds us that in fulfilling their needs, humans do not harm each other, in this case exchanging needs between members of society is a fair way. The rules of Allah that are unified and codified in the fiqh of mu'amalah cover several aspects of economic activities, one of which is buying and selling (al-ba'i). Buying and selling or referred to as Bai' is the exchange of property for property on the basis of mutual consent, or transferring property with a justified exchange. According to Sulaiman al-Asyqar, buying and selling is the exchange of property for property, or benefits for benefits in the form of transferring ownership and ownership. The term down payment is also known as DP (Down of Payment), advance payment, or down payment. In Indonesia this is regulated in Article 1464 of the Civil Code. The payment of a down payment or down payment in a buying and selling transaction is known by fiqh scholars as ba'i 'urbun. Ba'i 'urbun is a down payment paid by the buyer which shows that he is serious about his order. If the buyer then agrees on the ordered goods, a sale and purchase transaction is formed and the down payment is part of the agreed price of the ordered goods (assets). If the buyer later refuses to purchase the order, then the down payment is forfeited and becomes the property of the seller.